2023
DOI: 10.31098/ijeass.v3i1.1135
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Sustainable Growth Among Listed Non-Financial Firms in Nigeria During Financial Crisis: Does Board Characteristics Matter?

Abstract: During the worldwide financial catastrophe and pandemic, non-financial firms faced several challenges. Corporate survival in these difficult times necessitates the agitation for the long-term growth of the companies. Sustainable growth is defined as growth witnessed by a company in a stand-alone position without any outside finance. Sustainability in a term of long-term growth is obtained through the existence of effective qualities of the board of directors. There is indeed the existence of fantastic research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…We find that BOC size, independence, and gender affect CSR disclosure positively and significantly at the 1 per cent level. Our results are consistent with hypotheses 1,2,3, suggesting that the size, independence, and gender of BOC enhance CSR disclosure of the company (Kiliç et al, 2015;Harjoto & Rossi, 2019;Qa'dan & Suwaidan, 2019;Temiz & Acar, 2023;Asaolu et al, 2023). However, we find that the financial background of BOC is not associated with CSR disclosure.…”
Section: Comprehensive Board Of Commissioner Characteristics and Csrsupporting
confidence: 87%
See 1 more Smart Citation
“…We find that BOC size, independence, and gender affect CSR disclosure positively and significantly at the 1 per cent level. Our results are consistent with hypotheses 1,2,3, suggesting that the size, independence, and gender of BOC enhance CSR disclosure of the company (Kiliç et al, 2015;Harjoto & Rossi, 2019;Qa'dan & Suwaidan, 2019;Temiz & Acar, 2023;Asaolu et al, 2023). However, we find that the financial background of BOC is not associated with CSR disclosure.…”
Section: Comprehensive Board Of Commissioner Characteristics and Csrsupporting
confidence: 87%
“…In the case of Jordan, Qa'dan and Suwaidan (2019), also found that larger boards enhance the level of CSR disclosure. Asaolu et al (2023) recently reported a positive relationship between board size and sustainability growth based on listed firms in the Nigerian Exchange Group from 2011 to 2010. Based on previous empirical studies, we propose the hypothesis as follows: H1: Firms with larger BOC members are positively associated with corporate social responsibility disclosure, ceteris paribus.…”
Section: The Size Of Board Of Commissioner (Boc) and Corporate Social...mentioning
confidence: 99%